1999
DOI: 10.1002/(sici)1097-0118(199902)30:2<137::aid-jgt7>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Fast generation of regular graphs and construction of cages

Abstract: The construction of complete lists of regular graphs up to isomorphism is one of the oldest problems in constructive combinatorics. In this paper an efficient algorithm to generate regular graphs with given number of vertices and vertex degree is introduced. The method is based on orderly generation refined by criteria to avoid isomorphism checking and combined with a fast test for canonicity. The implementation allows to compute even large classes of graphs, like construction of the 4-regular graphs on 18 ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
167
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(173 citation statements)
references
References 5 publications
2
167
0
4
Order By: Relevance
“…From numerical experiments using GENREG software [6] and the cubhamg utility in the package nauty [5] on cubic graphs of various orders, we observe that bridge graphs constitute the majority of non-Hamiltonian graphs. Moreover, as the graph order N increases, so does the ratio of cubic bridge graphs over all cubic non-Hamiltonian graphs of the same order.…”
Section: A Conjecturementioning
confidence: 99%
“…From numerical experiments using GENREG software [6] and the cubhamg utility in the package nauty [5] on cubic graphs of various orders, we observe that bridge graphs constitute the majority of non-Hamiltonian graphs. Moreover, as the graph order N increases, so does the ratio of cubic bridge graphs over all cubic non-Hamiltonian graphs of the same order.…”
Section: A Conjecturementioning
confidence: 99%
“…Результаты для 4-, 5-и 6-регулярных графов представлены в таблице. Для генерации регулярных графов использовалась программы GENREG [5] и DSR Generator [6]. Вычисления показывают, что верхняя оценка может быть улучшена.…”
Section: рис 2 7-вершинный граф с Exp(g) =unclassified
“…This is further compounded by the constraint of a set global clustering coefficient. We therefore limited our investigations to possible configurations, as given in [16], with preliminary experiments used to determine realisable clustering coefficients by testing whether it was possible to find at least one valid network. We found that when limiting CF1 to its regularity component, it was always possible to find networks achieving a set level of global clustering.…”
Section: K-regular Networkmentioning
confidence: 99%